Spain leading the way in the truck’s cartel litigation. First rulings by the Spanish Supreme Court and their relevance in Europe - Bornemann, Ben; Suderow, Julia (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
In a series of 15 cassation judgments, the Supreme Court resolves fundamental issues for the private application of competition law within the Spanish jurisdiction, but which are projected to the rest of the Member States in very similar proceedings. These judgments analyse, among other things, the judge’s power to assess damages, the (non-) necessity of access to evidence inter partes, proportionality and the rules on economic expert testimony, as well as interests and limitation. The fifteen judgments condemned the members of the truck cartel to compensate various truck purchasers with a minimum of 5% of the purchase value plus interest. This cartel has generated the largest wave of antitrust litigation in Europe, both at national level and before the ECJ, which has already ruled on several occasions, most recently in the Tráficos Manuel Ferrer case.
Keywords: trucks; judicial estimation of the harm; cartel; Supreme Court; Tráficos Manuel Ferrer; access to evidence; econometry; private enforcement of competition law